Codependency and related health variables. - Martsolf DS; Sedlak CA; Doheny MO (Archives of Psychiatric Nursing, 2000)
Codependency is a controversial concept especially for feminist scholars who are concerned about pathologizing traditional female roles. This study's purpose was to determine: (1) the prevalence of codependency in a sample of older women who because of age may ascribe to traditional roles; (2) how the Hughes-Hammer/Martsolf theoretical model of codependency relates to other health variables; and (3) whether previous findings about the relationship between codependency and depression replicate. Survey design was used with a sample of 238 women (ages 65 to 91) attending a flu shot clinic. Subjects completed the Codependency Assessment Tool, Beck Depression Inventory, Quality of Life Scale, Perceived Health Report, Measurement of Patient Functional Abilities, and Illness Prevention Screening Behaviors Checklist. Of these women, 99% had low codependency scores. Statistically significant correlations existed between codependency and perceived health (p < .01), and functional ability (p < .01). Codependency was not significantly correlated with illness prevention behaviors and quality of life. Codependency and depression, as in previous studies, were significantly correlated (r = .446, p = .0001). Using analysis of variance, 3 codependency subscales had significant positive effect on depression: Low Self-Worth, Medical Problems, and Hiding Self. Further studies should examine the degree of ascribing to traditional female roles in women dealing with codependency issues. Copyright © 2000 by W.B. Saunders Company